Legal Protection of the Rights of the Child Victims in Indonesian Juvenile Criminal Justice System - Oksidelfa Yanto; Yoyon M. Darusman; Susanto Susanto; Aria Dimas Harapan (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2020)
This research purposes to observe the development of crimes against children in Indonesia. Firstly, will take a closer look toward the importance of child protection in family, school and the environment from violence and crime. Secondly, will evaluate how far the criminal justice system can give protection toward the children as victims of violence and crime. Thirdly, looking at the state responsibility in giving sanctions through the criminal justice system. The method used in this research is juridical-normative by collecting secondary data related to legislation and materials obtained from books, journals, and other relevant materials. The observation result shown that many children are victims of violence. The victimization is basically everywhere, not only at home, but also at school. Violence in schools is not merely physical violence, but also psychological. The responsibility for protecting, educating, and developing children lies in the environment, family, and school. The function of criminal law to fight crimes against children's rights is a major factor in the success of the juvenile criminal justice system.